Merritton, Ontario: The Rise and Decline of an Industrial Corridor (ca. 1845-1939) - Taylor, Robert (Scientia Canadensis, 1990)
ABSTRACTMerritton, Ontario, was a 19th-century boom town with many and various mills. This industrial corridor was largely the product of developments in technology, especially in transportation and communication. The Welland canals provided water power for industries and provided links to the wider world. Railways supplemented the canals. War needs and tariff policies helped the town's growth. Local entrepreneurs and town taxation policies played roles. Nevertheless, scientific discoveries applied to production were significant factors. Technological factors were equally important in contributing to the town's decline. Merritton's rise and fall shows how technology, both at the global and local levels, can create, nurture and abandon small human communities.